Generating solutions of a linear equation and structure of elements of the Zelisko Group - Victor Bovdi; Volodymyr Shchedryk; Bódi Viktor; Бовді Віктор; Щедрик Володимир (Elsevier, 2021)
Abstract. Solutions of a linear equation b=ax in a homomorphic image of a commutative Bezout domain of stable range 1.5 is developed. It is proved that the set of solutions of a solvable linear equation contains at least one solution that divides the rest, which is called a generating solution. Generating solutions are pairwise associates. Using this result, the structure of elements of the Zelisko group is investigated.
https://www.sciencedirect.com/science/article/abs/pii/S002437952100183X
Keywords: Linear equation; Stable range; Zelisko group; Lineáris egyenlet; Stabil tartomány; Zelisko csoport